Community Archive as a Platform for Development and Preservation of Intangible Heritage—the Community Archives Project - Portughies, Adi (Technical Annals, 2022)
BG archives have initiated the Community Archive Project, the objective being to create communal archives that will prepare the material for researching Israeli development towns and Bedouin communities from the bottom – up, fully digital and accessible online. Bedouin towns and development towns are home to thousands of Israelis, and their role in the historical development of the state of Israel is clear. That said, their particular stories have yet to be told, mainly due to the absence of accessible documentation. This ―silence of the archive‖, as it is called in archival studies, inhibits the development of effective research and creates the false impression that ―what you see is what you have‖. Because of the ―silence of the archives,‖ these communities have been portrayed in a similarly passive fashion in public discourse and scholarly research. Their natural growth and development, propelled by internal dynamics as organic communities with ―bottom up‖ growth, has, until now, received little attention from researchers. This project aims to address this gap and to enrich the historical record by including the archival collections of the development towns themselves. The project leans on the theoretical framework and moral motivation of the Canadian concept of Community Archive. We acknowledge that the fundamental challenge for this project is to create authentic archives that will reconstruct the silence of the archive. This paper discusses the meaning of this core challenge, the solutions we formulated and the significant impact this project is expected to have on the thriving field of Israel studies.